Aggressive behaviour in adolescent: the importance of biopsychosocial predictors among secondary school student s - Fauzi, Fatimah Ahmad; Zulkefli, Nor Afiah Mohd; Baharom, Anisah (Frontiers Research Foundation, 2023)
Introduction: Overt aggression is a common type of aggression observed among adolescents, which is apparent and outward confrontational acts manifested physically and verbally, such as fighting and shouting. It has become a major public health concern, as it results in detrimental health impacts like injury, mental health, and social problems. Methods: An observational study was conducted among 16-year-old school students to determine their biopsychosocial predictors, using stratified proportionate population sampling. Pre-tested surveys were distributed to measure students’ aggression, biological, psychological, and social factors. Results: A total of 463 students from four public secondary schools participated in the study, with a median aggression score was 23.00 (IQR=12.00). The significant predictors of aggression from multivariate analysis were Malay race, frequent dessert intakes, attitude towards aggression, low family income, and peer deviant affiliation (F [8, 244] = 15.980, p < 0.001, adjusted R2 = 0.290). Discussion: Adolescent aggression determinants are collectively impacted as a result of biological, psychological, and social predictors and need to be focused on in interventional strategies.